2018
DOI: 10.1097/md.0000000000012285
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mutation spectrum of common deafness-causing genes in Hakka newborns in southern China by semiconductor sequencing

Abstract: Hearing loss is a common neurosensory disorder, approximately half of the cases are caused by genetic factors, and approximately 70% of hereditary hearing impairments are nonsyndromic hearing loss (NSHL). The mutations of GJB2 (gap junction beta-2 protein), GJB3 (gap junction beta-3 protein), SLC26A4 (solute carrier family 26 member 4), and MT-RNR1 (mitochondrially encoded 12S RNA) are the most common inherited causes of NSHL. Because of different genetic backgrounds, the mutation spectrum of these common deaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Actually, c.IVS7-2 A>G mutation in SLC26A4 gene is the main mutation site of the large vestibular aqueduct syndrome in the Chinese population. This study discovers that the detection rate of c.IVS7-2 A>G mutation in SLC26A4 gene is the highest (1.53%), followed by c. 2168A> G, which is the same as the results in domestic literature [ 10 ]. Furthermore, studies have revealed that there are significant regional and ethnic differences in the site mutation of SLC26A4 gene.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Actually, c.IVS7-2 A>G mutation in SLC26A4 gene is the main mutation site of the large vestibular aqueduct syndrome in the Chinese population. This study discovers that the detection rate of c.IVS7-2 A>G mutation in SLC26A4 gene is the highest (1.53%), followed by c. 2168A> G, which is the same as the results in domestic literature [ 10 ]. Furthermore, studies have revealed that there are significant regional and ethnic differences in the site mutation of SLC26A4 gene.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, with cost-effective and rapid turnaround, the screening of large populations is feasible. Here, it should be noticed that the next-generation sequencing provides a stronger solution [ 10 , 14 ],whereas organizing massive population genetic screening is challenging, which also increases interpretation burden. In addition, the microarray platform shows excellent detection sensitivity to the heteroplasmic mitochondrial variants.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the chip-based SNP genotyping method was utilized in the detection of hereditary hearing-loss. Fifteen common mutations that cover over 80% of hereditary hearing-loss in China were chosen to construct a rapid screening tool for newborn babies. The specificity and sensitivity of the chip were carefully examined.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Hereditary hearing loss mainly involves four types: autosomal recessive inheritance (approximately 80%), autosomal dominant inheritance (approximately 15–20%), mitochondrial inheritance (approximately 1%) and sex-linked inheritance (approximately 1%) [ 4 ]. Based on a molecular epidemiological survey of deafness in China, GJB2, GJB3, SLC26A4 and mitochondrial 12S rRNA are the most universal deafness genes in Chinese [ 5 , 6 ]. The hereditary hearing loss resulting from GJB2 and SLC26A4 follows autosomal recessive inheritance.…”
Section: Introductionmentioning
confidence: 99%